Chapter 5.5 The Profession of Research Management and Administration in Canada - Deborah Zornes (Emerald Publishing Limited, 2023)
In Canada, the profession known as `research management' elsewhere across the globe, is mostly commonly referred to as `research administration' and encompasses activities and work associated with developing, administering, accounting for, and complying with sponsor requirements, guidelines, procedures, and laws relating to funded projects. Canada has a robust and active research administrator community through the Canadian Association of Research Administrators. As a result of changes beginning primarily in 2000, research administration has evolved to a complex, multifaceted profession with high demands for skills and expertise. Since 2000, there have been increased calls from research administrators in Canada to look at more formal professionalisation and certification of the research administrator role and to the evolution of the role to a profession. This chapter focusses primarily on those significant changes to the visibility and importance of research, and the subsequent growth of the profession of research administration in Canada.
10.1108/978-1-80382-701-820231038; 10.1108/978-1-80382-701-820231038; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262